Incidence and predictive value of social frailty among community-dwelling older adults in Southwest China: A prospective cohort study - Sun, Qian-qian; Tan, Ke; Tang, Hui-yu; Liu, Yan-yan; Zhu, Huan; Qin, Hai; Xia, Xin; Zhang, Min; Chen, Yan-yu; Nie, Shuang-shuang; Wang, Shuang (Frontiers in Public Health, 2023)
Background：Few studies have focused on the incidence and association of social frailty (SF) with adverse health events in Southwest China. This study aims to explore the predictive value of SF for adverse health events. Methods: A 6-year prospective cohort study was employed, participants completed two longitudinal follow-ups 3 and 6 years later. A modified social frailty screening index was used, adverse health events were evaluated by disability, hospitalization, falls, PF deterioration and mortality. Results: Among these participants, the median age was 71 years, 41.1% were male, and 71.1% were married or cohabiting. At baseline, 112 (24.3%) of 460 participants were classified as SF. It was observed that SF was closely associated with older (OR=1.04, 95% CI=1.00-1.07, P=0.047), having family members die in the past year (OR=2.60, 95% CI=0.93-7.25, P=0.068), having a mate (OR=0.40, 95% CI=0.25-0.66, P=0.000), and having family members to help with care (OR=0.53, 95% CI=0.26-1.11, P=0.092). The cross-sectional study demonstrated that SF was only significantly associated with disability (OR=12.89, 95% CI=2.67-62.13, P=0.001). Baseline SF significantly explained the incidence of mortality at the 3-year (medium-term, OR=4.89, 95% CI=2.23-10.71, P=0.000) and 6-year follow-ups (long-term, OR=2.22, 95% CI=1.15-4.28, P=0.017). Conclusion: SF prevalence was high in the Chinese older population. Older adults with SF had a significantly increased incidence of mortality at the longitudinal follow-up. Consecutive comprehensive health management of SF (eg. avoiding living alone and increasing social engagement) is urgently needed for the purposes of early prevention and multidimensional intervention in adverse health events, including disability and mortality.